Public awareness and attitudes towards marine protection in the United Kingdom. Issue 1 (15th October 2016) - Hawkins, Julie P.; O'Leary, Bethan C.; Bassett, Nicola; Peters, Howard; Rakowski, Sarah; Reeve, Georgina; Roberts, Callum M.
Abstract: Public perception research evaluating awareness and attitudes towards marine protection is limited in the United Kingdom (UK) and worldwide. Given public opinion can help drive policy and affect its successful delivery we conducted nationwide surveys in 2005, 2010 and 2015 to assess public knowledge of UK (England, Scotland and Wales) sea 'health' and management. Respondents from all three surveys were relatively pessimistic about sea 'health', perceiving this as poor-fair and largely in decline. Enthusiasm for marine conservation was high with almost two-thirds of respondents in each survey wanting > 40% of UK seas highly protected from fishing and damaging activities. In 2015 there was considerable dissatisfaction with the rate of progress in Marine Conservation Zone designation and over three-quarters of respondents considered dredging and trawling to be inappropriate in protected areas, contrary to management. The UK government and devolved administrations need to better align future conservation and management with public expectations. Highlights: 3 surveys conducted over 10 years assessed public awareness of UK marine protection. In each survey few perceived sea 'health' as good and > 33% thought it was declining. In 2015 respondents expressed considerable dissatisfaction with MCZ progress. Enthusiasm for MPAs was high in all surveys with the majority wanting > 40% coverage. Public opinion on MPA establishment and management conflicts with present practice.